Effect of different inorganic iron compounds on the biological methanation of CO2 sequestered in coal seams. (February 2021) - Xia, Daping; Huang, Song; Gao, Zhixiang; Su, Xianbo
Abstract: To study the effect of different inorganic iron compounds on the biological methanation of CO2 sequestered in coal seams, a biogas production experiment was carried out through use of bituminous coal D (China) and indigenous microorganisms, by adding bicarbonate and inorganic iron compounds. It is found that the addition of FeCl2 or FeS2 promoted methane production. FeS2 resulted in the highest methane concentration (30.54%) and methane production (0.191 mmol/g), which increased by 30.46% and 38.11%, respectively. The pH of the experimental group was lower than that of the control group during the whole process. The chemical oxygen demand (COD) first increased and then decreased, and the COD peak value greatest increased by 3.07% after FeCl2 was added. The ammonia nitrogen content in the liquid phase with FeCl2 or FeS2 was improved obviously (11.01% and 6.76%), and the microorganisms were increased accordingly. Scanning electron microscopy and energy dispersive spectrometry (SEM-EDS) showed that the microorganisms reacted with coal and iron after addition of Fe to generate several amorphous substances on the surface of coal, and further enhanced biomethane production. This study provides a new method for the utilization of CO2 sequestered in coal seams and the rational development of high sulfur coal. Highlights: FeS2 has the potential to increase the bio-methanation of sequestered CO2 . Change law of liquid phase parameters keep consistent with the biomethane generation. Microorganisms will react with coal and iron to promote the production of biomethane. Coal seams with high sulfur are suitable for the research of MECBM projects.